Studi identifikasi fase perkembangan tegakan menuju stadium iclimaks pada hutan primer di hutan produksi permanen dataran rendah Kalimantan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
Lowland permanent production forest for long-term timber production has been managed under polycyclic system for 35 years. This means that, almost the same amount of timber volume can be harvested under selective logging every 35 years and the designated stand before logging should be already situated in a steady state. This study dealt with the stand development of primary forest. Using the first measurement data 1996 from the national forest inventory project a question was investigated: how can the steady state in the primary forest be identified? The steady state was identified by the development phase of stand. To determine the phases, the diameter distribution of inventory plots was quantified with a linearized exponential function. Based on the parameter of the function, primary stands were classified into three phases using cluster analysis. This three phases were then described by stem number, basal area and tree volume. The result showed that the linearized exponential function could be used to describe the diameter distribution of primary stands. Using cluster method, the parameter of this function could be used as determining variables to classify the primary stands into three development phases, i.e. young phase, medium phase and old phase. By describing the phases with number of stems, basal area and tree volume revealed that these phases corresponded to the developmental process of the stand from young phase to maturity. It was then proposed that, the steady state was located in old phase.